KREATIVES HÖREN (CREATIVE LISTENING) IN THE CONTEXT OF SHARED LEARNING IN THE BRAZILIAN UNDERSTANDING AND ITS APPLICATION IN THE BRAZILIAN CHORAL WORK OF THE UFC CHOIR (Revista Docentes, 2024)
This article is dedicated to the Brazilian understanding of Shared Learning as a comparative foil to Kreatives Hören (Creative Listening), which was developed by the author and made fruitful for receptive and productive contexts. Creative listening has numerous overlaps with shared learning in the Brazilian understanding. There is also a great deal of overlap with the concerns of intercultural music education as they can be found in the German music education debate. Against this background, Kreatives Hören is presented as the basis or possibility of how the Brazilian choral work of the UFC Choir can be substantiated or enriched. The aim of this article is to work out the potential that Kreatives Hören has to realize shared learning in the Brazilian understanding. The first step is therefore to present the characteristics that have been identified in the Brazilian discussion on shared learning. In a second step, Kreatives Hören is presented on this basis and its potential in the context of shared learning in the Brazilian understanding is worked out. Finally, the extent to which Kreatives Hören can underpin and enrich the choral work of the UFC Choir will be worked out.